Raw ship-based Multibeam Sonar Data acquired during R/V Nathaniel B. Palmer expedition NBP0008 (2000) ... - Jacobs, Stan (Interdisciplinary Earth Data Alliance (IEDA), 2003)
This data set was acquired with a ship-based SeaBeam 2112 Multibeam Sonar system during Nathaniel B. Palmer expedition NBP0008 conducted in 2000 (Chief Scientist: Dr. Stan Jacobs). These data files are of MBSystem Compatible format and include Acoustic Backscatter, Swath Bathymetry, and Sidescan data that have not been processed. Data were acquired as part of the project(s): Shelf and Bottom Water Formation Near East Antarctic Polynyas and Glaciers and Circumpolar Deep Water and the West Antarctic Ice Sheet, and funding was provided by NSF grant(s): OPP97-25024 and OPP99-09374. ...